(untitled) (American Journal of Pedagogical and Educational Research, 2026)
Hydronyms constitute the most archaic and stable stratum of the English toponymic system. This paper investigates the linguistic characteristics, classification frameworks, and unique nominative behaviors of English water body names. Acting as “linguistic fossils” English hydronyms preserve ancient phonetic, morphological, and semantic structures despite centuries of language contact and replacement. Utilizing a diachronic and structural-semantic approach, the study classifies these hydronyms geographically, etymologically, and semantically.